The Implementation of Mosque-Based Islamic Education Programs in Schools - Ariyanti, Annisa; Moch. Bachrurrosyady , Amrulloh (Journal of Education and Religious Studies, 2023)
In today’s era, many children face challenges, including a declining interest in attending mosques and participating in mosque-related activities. Addressing this issue requires the collective effort of the government, parents, educators, the community, and other stakeholders. Schools, as key educational institutions, play a crucial role in instilling and applying religious values in children. Parents aspire for their children to be intelligent, pious, memorizing the Quran (hafidz), and deeply connected to the mosque. This aspiration inspired Laznas Nurul Hayat and the Khairunnas Education Foundation to introduce an innovative program: “School in the Mosque.” This study aimed to analyze the implementation of the mosque-based Islamic education program at SD Khairunnas 2 Surabaya and to identify the supporting and inhibiting factors affecting its execution. The study was conducted using a qualitative descriptive approach, utilizing observations, interviews, and documentation for data collection. Data analysis followed the Miles & Huberman model. Findings of this study indicated that the Khairunnas Education Foundation, established by LAZNAS Nurul Hayat in 2018 in Surabaya, is dedicated to enhancing education in Indonesia across various levels, from early childhood (KB-TK) to higher education (KEPQ). One of its key initiatives is SD Khairunnas 2 Surabaya, which has successfully implemented a mosque-based Islamic education program in collaboration with As-Shobirin Mosque and Al-Haq Mosque. The implementation of this program is influenced by four key factors: (1) communication, (2) resources, (3) disposition, and (4) bureaucratic structure.